Theatre the lively art - Wilson, Edwin 1927-; Goldfarb, Alvin (McGraw-Hill Education, 2022)
"Several qualities set Theatre: The Lively Art apart from other introductory texts. A particularly important element is our emphasis on the audience. All students reading the book are potential theatregoers, not just during their college years but throughout their lives. We have therefore attempted to make Theatre: The Lively Art an ideal one-volume text to prepare students as future audience members. It will give them a grasp of how theatre functions, of how it should be viewed and judged, and of the tradition behind any performance they may attend. In addition to serving as an ideal text for nonmajors, Theatre: The Lively Art will prepare students who wish to continue studies in theatre, as majors, minors, or students from other disciplines who take advanced courses"--Provided by publisher.